A plane model of the interaction of a vehicle with the road infrastructure. (March 2018) - Romero, J.A.; Lozano-Guzmán, A.A.; Obregón-Biosca, S.A.; Betanzo-Quezada, E.
Highlights: An integral computer program to simulate vehicle-infrastructure interaction, including pavements and bridges. The pavement and bridge are modelled by FEM beam-bar elements. Dynamic modulus for the asphalt mix beam depends on the temperature and the time loading rate. The Transition Matrix Approach is used, to create a computationally efficient program. Example results are presented on the effect of some parameters (speed, payload, road roughness and wheelbase dimension) on the infrastructure deflection. Abstract: In road transportation, bridges´ deck exhibit large deflections when compared with those of the pavements. The interaction of vehicles with these two types of road infrastructures signifies enormous costs for maintaining the whole infrastructure in economic operational conditions. In this paper, an integrated model for simulating the vehicle – infrastructure coupled interaction, is proposed. While the infrastructure model is based upon FEM, the vehicle considers a multibody model. A parametric analysis is carried out to analyse the effect of vehicle and infrastructure operational conditions, as well as vehicle design characteristics, on bridge and flexible pavement dynamic responses.